PENGARUH MANAJEMEN TALENTA, KONFLIK PERAN GANDA, DAN STRESS KERJA TERHADAP KINERJA KARYAWAN PT. BANK X CABANG KISARAN - JANTIANUS JANTIANUS; KHAIRUL KHAIRUL; REHULINA BANGUN; SYAHRUDIN MARPAUNG; SULAIMAN AHMAD (JURNAL ILMIAH MAKSITEK, 2023)
The biggest challenge of human resource management today is to win in the talent war. Talent war is a situation when the company racing against their competitor to obtain the best talent in the talent market.The one strategy to win this war talent is to implementing the use of talent management to define, discover, develop, manage, and retain talented employees in an effort to achieve strategic goals and future business needs. This study aims to determine and analyze the influence of talent management, multiple role conflicts and job stress on the performance of employees of PT Bank X Cabang Kisaran. This study is associative, ie research that connects two or more variables to see the effect of these variables. The population in this study were all 218 employees of PT Bank X Kisaran Branch. The number of samples in this study were 140 people with a proportional random sampling technique. The data used in this study is primary data and secondary data.. The analysis technique uses multiple linear regression analysis,with SPSS. The results of this study indicate that Talent Management, Multiple Role Conflict, and Job Stress simultaneously have a significant effect on the Performance of Bank X Employees. The partial test shows that Talent Management has a positive and significant effect on the Performance of Bank X Employees, Multiple Role Conflict has a negative and significant effect on performance. Bank X Employees and Job Stress have a negative and significant effect on the Employee Performance of Bank X.